2016
DOI: 10.29311/ndtps.v0i11.595
|View full text |Cite
|
Sign up to set email alerts
|

Supporting student transitions to placement and work: developing a new self-identity

Abstract: Moves towards the marketisation of higher education together with concerns over the challenges of graduate employment have led to an increased prioritisation of students undertaking relevant work experience while they study. Recognising a strong student demand for placements, universities are establishing employability initiatives including those designed to increase the availability of quality paid placements for students. To complement this activity, industry, sector-specific, regional placement projects suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Employers continue to place a high value on workers who have a mix of technical information communication technologies (ICT) capabilities and general enterprise skills (Deloitte, 2017). In addition, evidence indicates that employers, including those in IT, recruit for skills/competencies and experience as well as grades (Graduate Careers Australia, 2013;Webster et al, 2016). Furthermore, employers are looking for IT graduates with a mix of technical and business skills (Deloitte, 2016).…”
Section: The Discipline Of Itmentioning
confidence: 99%
See 1 more Smart Citation
“…Employers continue to place a high value on workers who have a mix of technical information communication technologies (ICT) capabilities and general enterprise skills (Deloitte, 2017). In addition, evidence indicates that employers, including those in IT, recruit for skills/competencies and experience as well as grades (Graduate Careers Australia, 2013;Webster et al, 2016). Furthermore, employers are looking for IT graduates with a mix of technical and business skills (Deloitte, 2016).…”
Section: The Discipline Of Itmentioning
confidence: 99%
“…The Graduate Outlook report by Graduate Careers Australia (2016) reported that for the sixth consecutive year graduates from IT were in especially high demand. However, it is becoming increasingly complex for IT graduates to negotiate the various and changing job roles that make up the IT industry, with a reported gap between employer expectations and graduate profiles (Webster et al, 2016). According to Meijers and Kuijpers (2014, p. 297), "career paths have become unpredictable and research and practice show that it is no longer possible to make career choices in a purely rational and information-based way".…”
Section: Introductionmentioning
confidence: 99%